Armenii droga do leninowsko-kemalowskiego rozbioru (1917–1921) - Adam Lityński (Czasopismo Prawno-Historyczne)
After the February Revolution of 1917 in Russia, the former nations of the Russian Empire searched for the possibility of forming their own independent countries. The situation was the same with three nations of Transcaucasia, namely Armenia, Azerbaijan and Georgia. After the separatist Treaty of Brest-Litovsk (signed on the 3rd of March 1918), Bolshevik Russia in practice gave away the Transcaucasia region to Germany and Turkey. Especially Turkey assumed an aggressive and annexationist stance at the time. And it was the Armenians who mainly put up the resistance. Armenia, together with Azerbaijan and Georgia, first created the Transcaucasian Democratic Federative Republic. However, the state was short-lived and it soon collapsed due to different approaches to preserving independence by the three countries. Azerbaijan tried to unite with Turkey, Georgia with Germany, while Armenia counted on the White movement Russians (led by General Denikin). Each of the three countries formed separate independent republics and one of them was the First Republic of Armenia. Germany and Turkey lost the First World War soon after but Caucasia was first attacked from the north by the White General Anton Denikin, who was supported by England and France. And later (in 1920) the country was invaded by the Bolsheviks. The Bolsheviks, thanks to the military might of the Red Army, overthrew the independent governments of those republics one by one. Subsequently, they introduced their own governments and annexed the countries into the Russian Soviet Federative Socialist Republic (RSFSR). The RSFSR signed the Treaty of Brotherhood with Turkey on the 16th of March 1921, which was mainly directed against Great Britain and France. In order to realize this alliance, Russia and Turkey divided between themselves the Armenian lands.